Extending high order derivatives for special differential equations of the form \(y’ = f(y)\) by using monotonically labeled rooted trees. - Hassani, Hossein; Dahaghin, Mohammad Shafie (International Journal of Applied Mathematical Research, 2015)
This paper presents a review of the role played by labeled rooted trees to obtain derivatives for numerical solution of initial value problems in special case \(y' = f(y), y(x_0) = y_0\). We extend a process to find successive derivatives according to monotonically labeled rooted trees, and prove some relevant lemmas and theorems. In this regard, the Â derivatives, of the monotonically labeled rooted trees with n vertices are presented by using the monotonically labeled rooted trees with k + n vertices. Eventually, this process is applied to trees without labeling.